Open-minded Environmental Education in the Science Classroom - Burns, David P.; Norris, Stephen P. (Paideusis, 2009)
In this paper we will discuss the issue of environmental advocacy in science education in light of William Hare’s concept of open-mindedness. Although we shall assume that science teaching and learning must go beyond the scientific facts and theories and deal with the implications of science for society, we shall argue that science education should also demand an open-mindedness about environmental concerns such that all proposals for sustainability and the like are weighed against the alternatives using the best scientific knowledge available. Our approach will be to describe two examples of environmental education that recommend insufficiently open-minded forms of teaching and a third example that avoids this shortcoming yet provides a sound basis in environmental education.